1680 Left ventricular filling pressure assessment with exercise stress echocardiography in patients with non-valvular atrial fibrillation. (17th January 2020) - Lara-Breitinger, K; Ullah, M W; Luong, C L; Padang, R; Oh, J K; Pellikka, P A; Mccully, R B; Kane, G C
Abstract: Background: Noninvasive parameters of LV filling pressure (E/e') and pulmonary pressures (RVSP) by Doppler echocardiography correlate with functional capacity and outcome in sinus rhythm (SR). Their role in AF is less clear. Elevated left ventricular filling pressures (E/e') and pulmonary artery systolic pressures (PASP) by Doppler stress echocardiography correlate with impaired functional capacity in patients in sinus rhythm (SR). However, there is limited data in atrial fibrillation (AF). Purpose: The aim of this study was to delineate the characteristics of patients with AF referred for exercise stress echocardiography and determine the prevalence and significance of E/e' and PASP elevations in AF. Methods: Subjects were patients referred for exercise treadmill stress echocardiography (n= 14, 937) and underwent regional wall motion assessment, Doppler assessment of mitral inflow (E) and early tissue relaxation (e') velocities and PASP at rest and immediately following maximum symptom limited exercise. Exclusion criteria included significant valvular heart disease (moderate or greater stenosis and/or regurgitation of any cardiac valve or previous valve repair or replacement) (1%), congenital heart disease (<1%) or refusal to participate in research (<1%). Results: Patients with AF (n = 310, 2%) were older (71 ± 10 vs 59 ± 13 years, p < 0.001). While resting blood pressure was similar, resting heart rates were higher in AF (80 ± 17 bpm vs 73 ± 13 bpm, p < 0.0001). AF patients achieved lower workloads (6.4 ± 2.4 METS vs 9 ± 2.4 METS, p < 0.001) with lower peak double products (22336 ± 6677 vs 25148 ± 5438, p < 0.001). Rates of resting (27% vs 10%, p < 0.0001) and exercise-induced (37% vs 20%, p < 0.0001) regional wall motion abnormalities were higher in AF. Mean E/e' was higher in AF at rest (12 ± 5 vs 9 ± 3, p < 0.001) and with exercise (12 ± 5 vs 10 ± 4, p < 0.001), with a higher percentage of patients in AF having E/e' ≥15 at rest (20% vs 6% in SR, p= <0.001) and with exercise in (23% vs 8%, p < 0.001). PASP was higher in AF at rest (33 ± 8 mm Hg vs 28 ± 6 mm Hg, p < 0.001) and with exercise (48 ± 12 vs 42 ± 11, p < 0.001) compared to SR. E/e' correlated with exercise capacity in AF and in SR, with an E/e' cutoff of 11.7 that was best predictive of impaired functional capacity (< 5 METS in women and < 7 METS in men). Conclusions: Abnormalities of E/e' and PASP are more prevalent in patients with AF and correlate with impaired functional capacity. In patients with AF, a medial E/e' ratio of ≥ 12 immediately following exercise is best associated with impaired functional capacity.